Nongray models for radiative absorption and anisotropic scattering by water droplets in fire CFD simulations. (March 2021) - Oluwole, Oluwayemisi O.; Gupta, Ankur; Wu, Bifen; Zhao, Xinyu; Meredith, Karl V.; Wang, Yi
Abstract: An efficient wide band radiation model is developed for absorption and scattering by water droplets in fires. The model applies eight spectral bands that enable coupling with radiating gas and soot media. Optical properties from the Mie theory are averaged within each band and tabulated for six droplet diameters within 10–1000 μm. The table is interpolated/extrapolated as needed during CFD simulations. An energy-conserving, finite-volume angular discretization is also described for efficiently computing anisotropic scattering. These approaches have been implemented in FireFOAM and are demonstrated using the standard emitting-receiving configuration, where a hot and a cold surface are separated by water droplets in transparent gases. The results show that the method conserves energy and predicts centerline incident fluxes within 1% of a previously published, high-fidelity benchmark. The typical normalization approach for energy conservation yields up to 100% error in the fluxes. Validation is performed against a detailed model that combines the Mie theory with a Monte Carlo Ray Tracing (MCRT) solver. Centerline fluxes are predicted within 10% of the detailed model. Gray model predictions are off by up to a factor of two. Finally, the scattering model is shown to introduce minimal overhead (only 15% of radiation solver time). Highlights: Efficient nongray model for absorption and scattering by water droplets in fires. Anisotropic scattering model conserves energy; more accurate than normalization. Validation performed using detailed Mie theory with Monte Carlo Ray Tracing (MCRT). Model predicted fluxes within 10% of MCRT benchmarks. Anisotropic model introduces negligible computational overhead (<15%).